Investment Policies to Extend the Life of Expressways in Japan - Hideo Noda; Yuichi Osano (Discrete Dynamics in Nature and Society)
This study examines the macroeconomic effects of investment policies aimed at extending the life of expressways in Japan based on a stochastic Ramsey model. The results of numerical analysis suggest that the benefits of life-extension investment in expressways can be increased by raising the level of maintenance intensity of expressways. The benefits of life-extension investment in expressways can be decomposed into the stock effect and the smoothing effect. Decomposition of life-extension benefits shows that the contribution of the stock effect is more than 90 percent, while that of the smoothing effect is less than 10 percent. The implementation of life-extension investment policies regarding expressways offers advantages in terms of reducing economic fluctuations and user charges. In addition, if relative risk aversion is high, efficiency is low and intergenerational equity is high. Furthermore, a higher level of technology leads to greater efficiency and intergenerational equity.